AN ANALYSIS OF STUDENTS’ ANXIETY IN SPAKING ENGLISH AT SMK KRISTEN 2 TOMOHON - Olivia Debora Lumeling; Nihta V. F Liando; Paula Hampp (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study was to describe the students' anxiety when speaking English in the eleventh grade at SMK Kristen 2 Tomohon. The goal of this study is to determine the extent of students' anxiety and the causes when speaking English. The qualitative method was employed in this study data gathered by observation and interview. According to the study's findings, 2 students (10%) are relaxed, 7 students (35%) reported mild anxiety, and 11 students (55%) are experiencing moderate anxiety. The factors cause anxiety are, they felt intimidated by the teacher, they did not understand or the material was difficult, they felt there was no preparation, or because the teacher did not explain clearly. It can be concluded that the majority of students have nervousness when speaking in English. It is crucial for English teachers to be paying attention. The teacher must provide encouragement to the students and speak confidently